Minimum wages, labor market institutions, and female employment and unemployment: A cross-country analysis - John T. Addison; Orgul Demet Ozturk (Institute for the Study of Labor (IZA), 2010)
This paper estimates the effect of minimum wage regulation in 16 OECD countries, 1970-2008. Our treatment is motivated by Neumark and Wascher's (2004) seminal cross-country study using panel methods to estimate minimum wage effects among teenagers and young adults. Apart from the longer time interval examined here, a major departure of the present study is the focus on prime-age females, a group typically neglected in the component minimum wage literature. Another is our deployment of time-varying policy and institutional regressors. Yet another is our examination of unemployment and participation outcomes in addition to employment effects. We report strong evidence of adverse employment effects among adult females and lower participation, even if the unemployment effects are muted. Although we report some similar findings to Neumark and Wascher as to the role of labor market institutions and policies, we do not observe the same patterns in the institutional data; in particular, we can reject for our target group their finding of stronger disemployment effects in countries with the least regulated markets.
Keywords: J20; J38; J48; J58; J88; 330; minimum wages; wage fixing machinery; prime-age females; employment; unemployment; participation; cross-section time-series data; OECD countries; labor market flexibility; labor market institutions and policies; Mindestlohn; Arbeitsmarktflexibilisierung; Frauenerwerbstätigkeit; Frauenarbeitslosigkeit; Schätzung; OECD-Staaten